ADHERENCE TO GOVERNANCE’S BEST PRACTICES AND ACCOUNTING INFORMATION QUALITY - Silva, Gabriela Cristina da (2018)
This study evaluates the impact of the adherence to governance’s Best Practices in accounting information quality. As a proxy to estimate governance’s Best Practices we have used company’s adhesion to the BM&FBOVESPA differentiated levels of corporate governance. As proxy to estimate the level of information quality, we have calculated the Quality Index for Accounting Information (IQIC), developed by Gabriel (2011), which encompass disclosure of information about cost of equity, Board of Directors’ fixed salary and variable remuneration, cash flows and value added statement and auditor's opinion. The sample comprised companies that integrated the Bovespa New Market and are also part of the Ibovespa Index. We analyzed the rates of 34 companies, before and after the adhesion to the New Market, through descriptive statistics and test for difference of means. Our data analysis shows that, even though the difference is not statically significant, Quality Index for Accounting Information had a small increase. Among the factors could have interfered in our analysis, there are limitations related to sample selection and the lack of control variables to explain the quality of accounting information.